2012
DOI: 10.1016/j.foodcont.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effectiveness of quick tests based on physical properties for the evaluation of used frying oil

Abstract: a b s t r a c tThe aim of this paper was to evaluate the effectiveness of the quick tests Viscofrit, Testo 265 and Fricheck in the monitoring of used frying oil for discarding, as a substitute for the measurement of total polar compounds (TPC), indicating the advantages and disadvantages of each test. Fifty-nine frying oil samples used to fry different types of food were evaluated using quick tests and the TPC open-column conventional method. The samples presented TPC values from 6.0 AE 1.1% to 39.2 AE 1.0%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 14 publications
4
27
1
Order By: Relevance
“…The equation that represented the model was TPC % (Testo 270) = -1.8229 + 0.5709*conventional method and the value found for the coefficient of correlation (r) was 0.69, explaining only 47.3% of the variation in the results of this quick test, which is considered insufficient. These results differ from those found by Dsawa et al (2012), who showed a correlation coefficient of r = 0.90 and R 2 of 80.5% from the Test 265 and the official methodology in 59 samples of palm olein and cotton oil in discarded frying oil. According to Bansal et al (2010), there are some disadvantages in the use of Testo 270, which included the presence of water, salt, minerals, long warm up time and the need of daily calibration factors that affect the polarity of a sample and can give false information on the TPC.…”
Section: Testo 270contrasting
confidence: 99%
See 1 more Smart Citation
“…The equation that represented the model was TPC % (Testo 270) = -1.8229 + 0.5709*conventional method and the value found for the coefficient of correlation (r) was 0.69, explaining only 47.3% of the variation in the results of this quick test, which is considered insufficient. These results differ from those found by Dsawa et al (2012), who showed a correlation coefficient of r = 0.90 and R 2 of 80.5% from the Test 265 and the official methodology in 59 samples of palm olein and cotton oil in discarded frying oil. According to Bansal et al (2010), there are some disadvantages in the use of Testo 270, which included the presence of water, salt, minerals, long warm up time and the need of daily calibration factors that affect the polarity of a sample and can give false information on the TPC.…”
Section: Testo 270contrasting
confidence: 99%
“…It has been reported that the test is imprecise and provides results that correlate poorly with total polar compounds (Dsawa et al, 2012). According that same author, the kind of oil /fat used or the type of food fried could indeed have had some influence, since the same kind of oils were dispersed and did not follow a linear pattern.…”
Section: Fri-checkmentioning
confidence: 99%
“…However, due to the complexity of the process, no single method can entirely measure the deterioration of oils in the frying process (PRISTOURI; BADEKA; KONTOMINAS, 2010). Some punctual diagnostics has already been performed about the oil quality and quality monitoring of oil or fat used in food service in several studies (STIER, 2004;BERTANHA et al, 2009;BANSAL et al, 2009;JUÁREZ et al, 2011;OSAWA et al, 2012;DAMY;JANIERI, 2004). They used rapid methods based in color.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of total polar compounds, that are formed through oxidation, thermal and hydrolytic reactions during frying, indicates the degree of deterioration in frying oil (Hampikyan et al 2011;Osawa et al 2012).…”
Section: Change In Total Polar Compounds (Tpc) Of Corn Oil During Fryingmentioning
confidence: 99%
“…The principle of the instrument is based on the measurement of changes in dielectric constant of frying oil and directly transform the data into the percentage in weight of polar compounds (Hampikyan et al 2011;Osawa et al 2012). When frying oil decompose thermally or through oxidation processes, its dielectric constant increases (Hein et al 1998).…”
Section: Change In Total Polar Compounds (Tpc) Of Corn Oil During Fryingmentioning
confidence: 99%